Deformation behaviour of TiN and Ti–Al–N coatings at 295 to 573K - Giuliani,F; Ciurea,C; Bhakhri,V; Werchota,M; Vandeperre,LJ; Mayrhofer,PH (Thin Solid Films, 2019)
Temperature-dependent nanoindentation testing was employed to investigate the deformation behaviour of magnetron sputtered (100) TiN and Ti1-xAlxN (x=0.34, 0.52, 0.62) coatings in the temperature range from 295 to 573K. The maximum temperature is sufficiently below the deposition temperature of 773K to guarantee for stable microstructure and stress state during testing. The TiN coating displayed the same hardness as bulk single crystal (SC) TiNbulk. The addition of aluminium to TiN (to form single-phase face centred cubic structured Ti1-xAlxN coatings) increased the room temperature hardness due to increased bond strength, lattice strain and higher activation energy for the dislocation slip. For coatings with a low aluminium content, Ti0.66Al0.34N, the decrease in hardness with temperature was similar to the TiN coating and SC-TiNbulk. In contrast, the hardness of coatings with moderate, Ti0.48Al0.52N, and high, Ti0.38Al0.62N, aluminium contents varied little up to 573K. Thus, the Ti1-xAlxN matrix is mechanically more stable at elevated temperatures than its TiN relative, by providing a lower decrease in lattice resistance to the dislocation flow with increasing temperature. The findings suggest that the addition of Al to TiN (to form Ti1-xAlxN solid solutions) not only improves the hardness but also leads to stable hardness with temperature, and emphasizes the importance of bonding states and chemical fluctuations, next to structure and morphology of the coatings that develop with changing the chemistry.